Manufacturing method of plate material for laminated iron core, plate material for laminated iron core, laminated iron core, and manufacturing method of laminated iron core

By employing Fe-Co-based soft magnetic materials and forming a thick insulating oxide film on laminated iron cores, the method addresses the limitations of existing technologies, achieving high-performance laminated cores with reduced iron loss and lower costs.

JP2025008032APending Publication Date: 2025-01-20铃木茂 +4
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023109869
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing methods for manufacturing laminated iron cores face limitations in increasing the resistance value and reducing iron loss, particularly for non-oriented steel sheets like permendur, and involve high manufacturing costs due to complex processes.

Method used

The use of Fe-Co-based soft magnetic materials with controlled annealing and application of a thick insulating oxide film formed by modifying metal alkoxide dispersion to enhance resistance and suppress eddy currents, eliminating the need for high-temperature magnesium treatment.

Benefits of technology

This approach results in a laminated core with a high space factor and reduced iron loss at lower manufacturing costs, utilizing Fe-Co-based soft magnetic materials with improved magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008032000001_ABST
    Figure 2025008032000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing a plate material for a laminated iron core, which makes it possible to obtain a high-performance laminated iron core having a large space factor and improved iron loss at low manufacturing costs by using an Fe-Co soft magnetic material, the plate material for the laminated iron core, the laminated iron core, and a method for manufacturing the laminated iron core.SOLUTION: A method includes an annealing step of annealing a steel sheet made of an Fe-Co based soft magnetic material containing 10 to 55 mass% Co, 0 to 4 mass% V, 0 to 1.5 mass% Al, with the remainder being Fe and unavoidable impurities, and a film forming step of modifying and drying a metal alkoxide dispersion to form a metal oxide film. In the annealing step, the steel sheet is subjected to a heat treatment at 400 to 900°C. In the film forming step, a metal oxide film having a thickness of 120 to 1000 nm is formed on the surface of the steel sheet.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a plate material for a laminated core, a plate material for a laminated core, a laminated core, and a method for manufacturing a laminated core. [Background technology]

[0002] Conventionally, laminated cores used in motors, small generators, turbine generators, transformers, etc. are formed by laminating soft magnetic materials having a high-resistance insulating coating on the surface in order to reduce induced iron loss. As a method for manufacturing a sheet material for the laminated core, a steel sheet containing 10% by mass to 55% by mass of Co, 0% by mass to 4% by mass of V, 0.1% by mass to 1.5% by mass of Al, with the balance being Fe and unavoidable impurities, is heated at an oxygen partial pressure of 1×10 -26 Pa~1×10 -14 A method has been developed for producing a laminated core sheet material having an oxide film mainly composed of Al on the surface by heat treating the sheet material at 700° C. to 950° C. in an atmosphere of 1 Pa (see, for example, Patent Document 1).

[0003] Also, a method for producing grain-oriented electrical steel sheet has been disclosed in which an organic solvent-based insulating coating treatment liquid containing an alkoxide and oxide fine particles having a particle size in the range of 10 to 100 nm is applied to the surface of grain-oriented electrical steel sheet after final annealing, and then the steel sheet is subjected to a heat treatment while maintaining the steel sheet temperature in the range of 200 to 800°C (see, for example, Patent Document 2).

[0004] As a method for forming an insulating film on a silicon steel sheet, a method has been disclosed in which an organic solvent solution containing one or more metal alkoxides is applied to the surface of a silicon steel sheet having a thickness of 0.2 mm or less, and then the sheet is dried and annealed to form an insulating film made of a metal oxide (see, for example, Patent Document 3). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2020-202314 A [Patent Document 2] Japanese Patent Publication No. 60-258477 [Patent Document 3] Japanese Patent Application Publication No. 6-215622 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the method described in Patent Document 1 has a problem that it is difficult to increase the resistance value and improve the iron loss because there is a limit to the thickness of the oxide film that can be formed. Also, it was thought that if the insulating oxide film becomes thick, the space factor of the soft magnetic material will be small even if the plate material is laminated to manufacture a laminated core.

[0007] The method of Patent Document 2 requires high-temperature treatment in the presence of magnesium to form a forsterite layer before coating preparation, which requires many manufacturing steps and increases manufacturing costs.In addition, the methods of Patent Documents 2 and 3 are based on the principle of reducing iron loss by applying coating tension to grain-oriented electrical steel sheet, so they were thought to be inapplicable to improving iron loss in Permendur, a non-oriented steel sheet.

[0008] The present invention has been made with attention to these problems, and has an object to provide a method for manufacturing sheet material for laminated cores, which utilizes an Fe-Co-based soft magnetic material and makes it possible to obtain high-performance laminated cores with a large space factor and improved iron loss at low manufacturing costs, a sheet material for laminated cores, the laminated cores, and a method for manufacturing the laminated cores. [Means for solving the problem]

[0009] As is known from the Slater-Pauling curve, Fe-Co alloys show the maximum magnetic flux density as bulk metals, centered around 35 Co. Therefore, the inventors of the present invention have conducted research aimed at utilizing this high magnetic flux density Fe-Co soft magnetic material to increase the space factor when laminating sheets, by thickening the insulating oxide film to increase the resistance, thereby suppressing the generation of eddy currents and reducing iron loss, and have arrived at the present invention.

[0010] In other words, the manufacturing method of the sheet material for laminated cores according to the present invention is characterized by having an annealing step of annealing a steel sheet made of an Fe-Co based soft magnetic material containing 10 to 55 mass % Co, 0 to 4 mass % V, 0 to 1.5 mass % Al, with the remainder being Fe and unavoidable impurities, and a coating formation step of modifying a metal alkoxide dispersion and drying it to form a metal oxide coating.

[0011] In the manufacturing method of the laminated core sheet material according to the present invention, the raw steel sheet is made of a Fe-Co soft magnetic material, and therefore the material has high performance. In addition, in the manufacturing method of the laminated core sheet material according to the present invention, a thick insulating oxide film is formed in the film formation process, and the resistance value is increased, thereby suppressing the generation of eddy currents and reducing iron loss. This makes it possible to increase the space factor when the sheets are laminated, and to obtain a high-performance laminated core. In addition, since there is no need to perform a high-temperature treatment in the presence of magnesium before preparing the film to form a forsterite layer, the manufacturing process is reduced, and the laminated core sheet material can be manufactured at low cost.

[0012] In the method for manufacturing a plate material for laminated core according to the present invention, the steel plate is preferably subjected to a heat treatment at 400 to 900°C in the annealing step, and more preferably to a heat treatment at 700 to 900°C. In the film forming step, the metal oxide film having a thickness of 120 to 1000 nm is preferably formed on the surface of the steel sheet. In this case, the resistance value can be effectively increased, the amount of eddy current generated can be suppressed, and iron loss can be reduced.

[0013] After the surface of the steel sheet is modified with the metal alkoxide dispersion in the film forming step, it is preferable to wash the surface with water and then dry the surface. In this case, the thickness of the metal oxide film can be made more uniform. The number of times of washing with water may be one or more. The method of modifying the metal alkoxide dispersion liquid may be, for example, coating, spraying, immersion, or other adhesion methods. The number of modifications, for example, the number of coatings, sprayings, or immersion, may be one or more. The thickness can be adjusted by multiple modifications. The method of drying after modification may be, for example, natural drying, heat drying, or vacuum drying, or other methods.

[0014] The metal alkoxide dispersion preferably contains one or more metal alkoxides of Al, Si, Cr, Zr, Li, Ti, and Mg. Examples of the types of alkoxides include alkoxy groups such as methoxy, ethoxy, propoxy, and butoxy. Examples of metal alkoxides include aluminum butoxide, aluminum (iso)propoxide, methyl silicate, ethyl silicate, zirconium methoxide, zirconium ethoxide, zirconium (iso)propoxide, zirconium butoxide, titanium ethoxide, titanium (iso)propoxide, and titanium butoxide. The metal alkoxide dispersion may be a composite alkoxide containing two or more metals, such as a bimetallic alkoxide or a trimetallic alkoxide.

[0015] Examples of the liquid to be dispersed include alcohols such as methyl alcohol, ethyl alcohol, (iso)propyl alcohol, and butyl alcohol; aromatic solvents such as toluene and xylene; esters such as ethyl acetate, butyl acetate, and methyl lactate; glycols such as polyethylene glycol and hexylene glycol; and glycol ethers such as ethylene glycol monobutyl ether and ethylene glycol monopropyl ether. Powder of the metal to be used may be added to the metal alkoxide dispersion liquid, and the pH of the metal alkoxide dispersion liquid may be adjusted. The concentration of the metal alkoxide dispersion is preferably 0.2% by mass or more. The metal alkoxide dispersion is preferably an aluminum butoxide dispersion.

[0016] The steel plate preferably contains 40 to 53 mass % of Co and 1 to 2 mass % of V. The steel plate may be made of a rolled plate or other steel plate. The film forming step may be carried out after the annealing step. The annealing step may be carried out after the film forming step. When the annealing step is carried out after the film forming step, it is preferable to perform a heat treatment in the annealing step by gradually increasing the temperature of the steel sheet from 0 to 100°C to 700 to 900°C. The heat treatment time is preferably 10 minutes to 3 hours, particularly preferably 10 to 60 minutes. The temperature increase rate in the heat treatment is preferably 90°C / min or less. The heat treatment atmosphere preferably contains hydrogen and has a dew point of -50°C or less.

[0017] The sheet material for laminated core according to the present invention is characterized in that it has a metal oxide film having a thickness of 120 to 1000 nm on the surface of a steel sheet made of an Fe-Co based soft magnetic material containing 10 to 55 mass % Co, 0 to 4 mass % V, 0 to 1.5 mass % Al, 0.001 to 0.02 mass % O, with the remainder being Fe and unavoidable impurities. The laminated core plate material according to the present invention can be suitably manufactured by the above-mentioned method for manufacturing the laminated core plate material according to the present invention.

[0018] In the present invention, V and Al are optional components and may not be contained, that is, the V and / or Al in the steel sheet may be 0 mass %. The steel sheet preferably contains 40 to 53 mass % of Co and 1 to 2 mass % of V. In this case, deterioration of workability due to ordering embrittlement can be improved. The laminated core plate material according to the present invention preferably has a space factor of 98% or more. In this specification, the space factor is the ratio of the area of ​​the portion excluding the oxide film (the portion that is not oxidized) to the cross-sectional area of ​​the laminated core plate material. The steel sheet preferably has a saturation magnetic flux density of 2.2 Tesla or more and a coercive force of 2 A / cm or less.

[0019] A laminated core according to the present invention is characterized in that it is formed by laminating the above-mentioned laminated core plate materials. The manufacturing method of the laminated core according to the present invention is characterized in that a plurality of steel plates made of an Fe-Co based soft magnetic material each containing 10 to 55 mass % Co, 0 to 4 mass % V, 0 to 1.5 mass % Al, with the remainder being Fe and unavoidable impurities, are modified with a metal alkoxide dispersion liquid and dried to produce a metal oxide film, and the metal oxide films of each steel plate are overlapped and annealed while applying pressure perpendicular to each steel plate, thereby joining the overlapped metal oxide films. The laminated core manufacturing method according to the present invention allows the laminated core according to the present invention to be manufactured more easily and effectively than diffusion bonding. The pressure applied is preferably 80 to 200 kPa. The annealing temperature is preferably 400 to 900°C, and more preferably 700 to 900°C. The annealing time is preferably 10 minutes to 3 hours, and more preferably 10 to 60 minutes. The conditions for the steel plate, metal alkoxide dispersion, metal oxide film, etc., can be the same as those described above.

[0020] In the present invention, the steel sheet preferably contains 46% by mass to 50% by mass of Fe as the balance. The amount of unavoidable impurities is preferably 10% by mass or less, and more preferably 1% by mass or less. Examples of the unavoidable impurities include one or more of C, Si, and Mn. Examples of the unavoidable impurities include one or more of Cr, Nb, Mo, W, Ni, and Ti. The total amount of these unavoidable impurities is preferably 1% by mass or less. Effect of the Invention

[0021] According to the present invention, it is possible to provide a manufacturing method for sheet material for laminated cores, which utilizes an Fe-Co-based soft magnetic material and makes it possible to obtain high-performance laminated cores with a large space factor and improved iron loss at low manufacturing costs, the sheet material for laminated cores, the laminated cores, and a manufacturing method for laminated cores. [Brief description of the drawings]

[0022] [Figure 1] FIG. 11 is a state observation diagram showing the surface state at each heat treatment temperature in Example 2 of the present invention. [Diagram 2] 1 is a graph showing the coating thickness and electrical resistance value when modified once with a metal alkoxide dispersion, modified five times, and produced by a dry method in Example 3 of the present invention. [Diagram 3] 10 is a graph showing the analysis results by X-ray photoelectron spectroscopy of the laminated core plate material manufactured in Example 3 of the present invention. [Figure 4] 11 is an enlarged optical microscope photograph of a coating bonding surface of a laminated core manufactured in Example 4 of the present invention. Example 1

[0023] Various embodiments of the present invention will now be described with reference to the drawings. A rolled steel sheet of a soft magnetic material of Fe-Co system consisting of 48% Co by mass, 48% Fe by mass, 2% V by mass, and the remainder consisting of unavoidable impurities was prepared. First, the raw materials containing each element were melted in a vacuum induction melting furnace, and an ingot (diameter about 80 mm) of about 7 kg including a riser was prepared. Next, each ingot was formed into a thickness of 20 mm by hot forging, and further rolled to a thickness of 4 mm by hot rolling. After each rolled sample was subjected to solution treatment, it was mechanically polished to the equivalent of #400, and rolled to a thickness of 0.35 mm by cold rolling. A test piece with an outer diameter of 45 mm, an inner diameter of 33 mm, and a thickness of 0.35 mm was cut out from the polished sample, and the surface was cleaned by mirror polishing. In this way, a test piece of a thickness of 0.35 mm consisting of a rolled steel sheet of a soft magnetic material made of Fe-Co alloy was prepared.

[0024] The test piece was subjected to an annealing process and a coating formation process to manufacture a laminated core sheet material of Example 1. In the annealing process, the test piece was heated at 830°C for 3 hours in a vacuum or a hydrogen atmosphere. In the coating formation process, the test piece was modified with an aluminum butoxide dispersion liquid and then naturally dried.

[0025] In the film formation process, 27 parts by mass of aluminum butoxide was dissolved in 50 parts by mass of water and heated to 91°C, after which 11 parts by mass of ethyl acetylacetone was added, followed by 1 part by mass of nitric acid to prepare a sol-like aluminum butoxide dispersion. After immersing the test pieces in the aluminum butoxide dispersion, they were washed with pure water and dried to form an oxide film. Two types of laminated core plate materials were manufactured, one in which the film was applied after magnetic annealing, and the other in which the film was applied and magnetic annealed.

[0026] The test conditions and the various measurement results of the manufactured laminated core plate materials are shown in Table 1. For comparison, test pieces were prepared that were not subjected to magnetic annealing and were only coated with a coating.

[0027] [Table 1]

[0028] As shown in Table 1, both test pieces 1 and 2 had excellent magnetic properties, and high-performance laminated core plate materials could be manufactured. Example 2

[0029] The mechanically polished sample prepared by the method of Example 1 was cut into 10 mm squares and mirror-polished to clean the surface. Thus, a 0.35 mm thick test piece was prepared from a rolled steel sheet of soft magnetic material made of an Fe-Co alloy. The test piece was immersed once in the aluminum butoxide dispersion prepared by the method of Example 1 and dried to generate an Al oxide film. The test piece was heated from room temperature 20°C to 700°C at a heating rate of 100°C / hour, and annealed to produce a plate material for laminated iron cores. The surface state for each 100°C heating is shown in Figure 1. As shown in Figure 1, the oxide film surface had a metallic luster up to 300°C, showed an interference color at 400°C, and showed low reflectance at 700°C. Example 3

[0030] A test piece made of rolled steel plate was prepared by the method of Example 2. The test piece was immersed in the aluminum butoxide dispersion liquid prepared by the method of Example 1, and dried to generate an Al oxide film. The test piece was magnetically annealed to produce a laminated iron core sheet material of Example 3. Also, as a comparative example, a laminated iron core sheet material having an Al oxide film on its surface was produced by a dry method. In the dry method, a rolled steel plate consisting of 48 mass% Co, 48 mass% Fe, 2 mass% V, 0.25 mass% Al, and the remainder unavoidable impurities was subjected to magnetic annealing at an oxygen partial pressure of 1×10 -26 Pa~1×10 -10 The laminated core plate material was then heat-treated at 900°C for 1 hour in an atmosphere of 10 Pa to produce a laminated core plate material. The number of times of immersion in the aluminum butoxide dispersion liquid, the heating temperature and heating time of magnetic annealing in this Example 3, and the oxide film thickness and sheet resistance measured by an ellipsometer for the laminated core plate material produced in this Example 3 and the laminated core plate material produced by the dry method are shown in Figure 2.

[0031] As shown in FIG. 2, the thickness of the oxide film formed by the dry method is limited to 100 nm, whereas in Example 3, the thickness can be made larger than 100 nm, and the resistance value can be increased by 6 to 25 times compared to the dry method. Additionally, the laminated core plate material that had been modified five times was analyzed by X-ray photoelectron spectroscopy. The results are shown in Figure 3. As shown in Figure 3, the formation of alumina (Al2O3) in the oxide film can be confirmed, and the formation of an insulating film can be confirmed from the valence band spectrum band gap. Example 4

[0032] Two test pieces made of rolled steel plates were prepared by the method of Example 2. The two test pieces thus prepared were each immersed five times in the aluminum butoxide dispersion liquid prepared by the method of Example 1, and then dried to generate an Al oxide film. The Al oxide films of the test pieces were overlapped and annealed at 700°C for two hours while applying a vertical load pressure of 120 kPa to each steel plate, and the overlapped Al oxide films were bonded to produce a laminated core. An optical microscope enlarged photograph of the film bonding surface of the manufactured laminated core is shown in FIG. 4. This method enabled the two test pieces to be firmly bonded, and the laminated core could be manufactured more easily and effectively than diffusion bonding.

Claims

1. A method for manufacturing a plate material for laminated iron cores, comprising an annealing step of annealing a steel plate made of an Fe-Co based soft magnetic material containing 10 to 55 mass% Co, 0 to 4 mass% V, 0 to 1.5 mass% Al, with the remainder being Fe and unavoidable impurities, and a film forming step of modifying a metal alkoxide dispersion and drying it to form a metal oxide film.

2. 2. The method for manufacturing a laminated core plate material according to claim 1, wherein the steel plate is subjected to a heat treatment of 400 to 900° C. in the annealing step.

3. 3. The method for manufacturing a plate material for laminated cores according to claim 2, wherein the metal oxide film having a thickness of 120 to 1000 nm is formed on the surface of the steel plate in the film forming step.

4. 4. The method for manufacturing a plate material for laminated cores according to claim 3, wherein after the surface of the steel plate is modified with the metal alkoxide dispersion in the film forming step, the steel plate is washed with water and then dried.

5. 5. The method for manufacturing a plate material for a laminated core according to claim 4, wherein the steel plate contains 0 mass % of Al.

6. 6. The method for manufacturing a laminated core plate material according to claim 5, wherein the steel plate contains 40 to 53 mass % of the Co and 1 to 2 mass % of the V.

7. 7. The method for manufacturing a laminated core sheet material according to claim 1, wherein the film forming step is performed after the annealing step.

8. 7. The method for manufacturing a laminated core plate material according to claim 1, wherein the annealing step is performed after the film forming step.

9. 9. The method for manufacturing a laminated core plate material according to claim 8, wherein the heat treatment is performed by gradually increasing the temperature of the steel plate from 0 to 100° C. to 700 to 900° C. in the annealing step.

10. A sheet material for laminated iron cores, comprising a steel sheet made of an Fe-Co based soft magnetic material containing 10-55 mass% Co, 0-4 mass% V, 0-1.5 mass% Al, 0.001-0.02 mass% O, with the remainder being Fe and unavoidable impurities, and having a metal oxide film having a thickness of 120-1000 nm on the surface thereof.

11. The laminated core plate material according to claim 10, characterized in that the steel plate contains 0 mass % of Al.

12. The laminated core plate material according to claim 11, characterized in that the steel plate contains 40 to 53 mass % of the Co and 1 to 2 mass % of the V.

13. 13. The laminated core sheet material according to claim 12, characterized in that the space factor is 98% or more.

14. 14. The laminated core sheet material according to claim 13, wherein the steel sheet has a saturation magnetic flux density of 2.2 tesla or more and a coercive force of 2 A / cm or less.

15. A laminated core, comprising the plate material for a laminated core according to any one of claims 9 to 14 laminated together.

16. A method for manufacturing a laminated core, comprising the steps of modifying a plurality of steel plates made of an Fe-Co based soft magnetic material each containing 10 to 55 mass % Co, 0 to 4 mass % V, 0 to 1.5 mass % Al, with the remainder being Fe and unavoidable impurities, with a metal alkoxide dispersion liquid, drying the modified steel plates to form a metal oxide film, overlapping the metal oxide films of the steel plates, and annealing the steel plates while applying pressure perpendicular to the steel plates, thereby bonding the overlapped metal oxide films.

Citation Information

Patent Citations

  • Formation of insulating film on silicon steel sheet

    JP1985258477A

  • Directional electromagnetic steel sheet with insulating film excellent in processability and heat resistance, and its manufacture

    JP1994215622A

  • Method for manufacturing plate material for laminate iron core, plate material for laminate iron core, and laminate iron core

    JP2020202314A